2020
DOI: 10.1002/app.49969
|View full text |Cite
|
Sign up to set email alerts
|

Phase morphology evolution and thermally conductive networks of immiscible polymer blends

Abstract: The selective distribution of fillers in multi-phase polymer blends was dramatically studied to deal with thermal management fields issues. Concerning thermodynamic and kinetic effects of fillers on immiscible polymer blends, the compatibilization of fillers on phase morphology evolution and final construction of thermal conductive pathways were rarely discussed. In this work, BN fillers and polar dispersed phase were introduced into PE through various processing methods. The result showed that filler-coated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Figure 6c,d indicates that there is an obvious reduction of the values of tan 𝛿 and a shear thinning behavior with respect to frequency for PC/BN/CNT2 composites when compared with that of PC/BN counterparts, which is characteristic of solid-like response behavior. [33] Thus, it can be concluded that physically interconnected network can be readily formed with the introduction of a small amount of CNTs (2 wt%) in PC/BN composites, which is viable for improving the 𝜆 of polymer composites.…”
Section: Rheological Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6c,d indicates that there is an obvious reduction of the values of tan 𝛿 and a shear thinning behavior with respect to frequency for PC/BN/CNT2 composites when compared with that of PC/BN counterparts, which is characteristic of solid-like response behavior. [33] Thus, it can be concluded that physically interconnected network can be readily formed with the introduction of a small amount of CNTs (2 wt%) in PC/BN composites, which is viable for improving the 𝜆 of polymer composites.…”
Section: Rheological Behaviormentioning
confidence: 99%
“…The testing voltage was 100 V. Dielectric measurement was performed over a frequency range of 10 1 -10 6 Hz by a Novocontrol Concept 50 system which was equipped with an Alpha impedance analyzer (Novocontrol Technologies GmbH & Co. KG, Germany). [32][33][34][35][36][37][38][39][40][41] d) Schematic diagram of heat conduction mechanism.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For increasingly significant TC of polymer composites, an effective strategy consists of forming percolated filler networks within the polymer. When reaching the percolation threshold, the heat transfer will be more efficient while the interfacial thermal resistance will be minimized [20,24,41,[53][54][55][56][57][58][59][60]. This morphology can be obtained by dispersing the fillers in one of the two co-continuous phases of an immiscible polymer blend.…”
Section: Introductionmentioning
confidence: 99%